Development of E-Handouts as Teaching Materials for the Sub-Concept of the Human Sensory System in Senior High School - Wasilah, Elis Shofiyatul; Kaspul, Kaspul; Azizah, Aulia (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
This study aims to describe the validity, readability, and student responses regarding the e-handout on the sub-concept of the human sensory system for 11th grade at SMA/MA. This type of research is a research and development study using the ADDIE model. The research is limited to the Development stage. Data analysis techniques are obtained through validity, readability, and student response tests. The results of the research were developed into an E-Handout. Based on the validity test results, the suitability achieved a percentage of 85,81% (very valid), and the feasibility validation received 87,11% (very valid). The readability test received a percentage of 88,68% (perfect). The student response test obtained a percentage of 89,15% (very good). This research highlights the importance of integrating technology into education and supporting the development of digital competencies among students relevant to the times' demands. The e-handout can enhance students' interest and engagement in learning, given the use of interactive and easily accessible digital learning materials. The conclusion is that the developed E-Handout has several unique characteristics, making it an engaging learning resource. These include a systematic presentation of material supported by clear images and illustrations.